Comparação entre os sistemas de classificação citopatológica e histopatológica para as neoplasias mamárias malignas em cadelas - Furtado, Adriana Pereira (2016)
There are currently a large number of canine related cancers, with mammary tumors having the highest incidence in bitches. Although histopathological examination is recommended as a definitive diagnosis, cytopathology has shown good levels of cyto-histopathological concordance. The screen study had the purpose of verifying the accuracy of cytopathological examination in the diagnosis of breast neoplasms in bitches, whose method implies a safer, less invasive procedure and a fast result. It was carried out in the Animal Pathology Sector of the Veterinary and Zootechnical School of the Federal University of Goiás and in a veterinary clinic in the city of Goiânia, Goiás. The cytopathological and histopathological diagnosis of 43 bitches with malignant mammary neoplasias was analyzed. The cytological exams were performed by applying the fine needle aspiration method and the results were analyzed using the histopathological diagnosis as confirmatory. The histopathological classification used was that recommended by the World Health Organization for canine mammary tumors and updated by Goldschmidt in 2001. This study revealed an accuracy of more than 90% of the cytopathological examination. The most frequent malignant mammary neoplasia diagnosed in the histopathology was the complex carcinoma (22%). The efficacy of 1% Methylene Blue dye on Sentinel Lymph node marking was assessed during the mastectomy procedure, and this was shown to be excellent for such labeling. Regarding foci of regional or distant metastases, it was found that tumors considered more malignant such as anaplastic carcinoma and micropapillary carcinoma formed more metastases than the other histological types.